Toxicokinetics of Ethyl Tertiary Butyl Ether in the human body - Arndt, Megan (My University, 2007)
Millions of people have been exposed to the gasoline additives MTBE and ETBE, while little is known about how quickly the body excretes these chemicals. Our study uses powerful mathematical techniques to estimate how quickly, and with how much variability, a population of volunteers exposed to these chemicals excretes them.
Population kinetic analysis of MTBE and ETBE exposures
Poster with text and graphs describing research conducted by Megan Arndt advised by Crispin Pierce.
Keywords: Gasoline--Additives; Butyl methyl ether--Health aspects; Reformulated gasoline--Toxicology; Posters; Butyl methyl ether--Toxicology; Gasoline--Toxicology; Motor fuels--Toxicology; Motor fuels--Additives